Pengaruh Tekanan Waktu Dan Independensi Terhadap Kualitas Audit: Studi Pada Kantor Akuntan Publik di Wilayah Malang - Rizal, Noviansyah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
This study aimed to determine the effect of time pressure on audit quality and independence of a Public Accounting Firm (KAP) in Malang. The sample used by 40 respondents, that are auditors that have been working in 8 KAP of Malang. Meanwhile, to answer the research hypotheses using multiple regression analysis and then performed classical assumption.Based on the results of this study, we can be concluded that the independence has influenced of an audit quality. So the higher the attitude held by an independent auditor will improve audit quality. While the time pressure has not influenced of an audit quality. It can beconcluded that the pressure of time made by the auditor will lower the quality of the audit and audit reporting